ANALISIS STRUKTUR FISIK PUISI â€œTIDAK ADA NEW YORK HARI INIâ€ KARYA M. AAN MANSYUR - desty nur wahyuni (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Literary work is a representation or outpouring of an author's heart, it can be expressed in oral or written form. Poetry includes pouring out ideas or feelings of the heart using figurative language. Writing poetry is usually used to criticize or express an event. The physical structure of poetry in New York today by M. Aan Mansyur is more towards an attempt to express expression indirectly. The writer chooses the poem by M. Aan Mansyur to be used as a research, this is meant to understand the physical structure of the poem. This research uses descriptive method, which aims to carry out a systematic, factual, and accurate description of the physical structure of the poetry. The results of the discussion in poetry that there is no New York today found the meaning of homesickness, longing for lovers, and homesickness and researchers were able to reveal the meaning contained in poetry in terms of diction, imagery, concrete, figurative language, rhyme, facial expression, and mandate